Direct-gap semiconducting tri-layer silicene with 29% photovoltaic efficiency. (September 2018) - Lv, Jian; Xu, Meiling; Lin, Shiru; Shao, Xuecheng; Zhang, Xinyu; Liu, Yanhui; Wang, Yanchao; Chen, Zhongfang; Ma, Yanming
Abstract: Crystalline silicon is dominating the current solar cell market due to the significant efficiency improvement and cost reduction in last decades. However, its indirect band gap nature leads to inefficient visible-light absorption, which seriously impedes further performance enhancement in silicon-based photovoltaic devices. Thus, it is highly desirable to develop direct band gap silicon materials. Herein, by means of ab initio swarm-intelligence structure-searching method, we predicted a quasi-direct gap semiconducting tri-layer silicene structure consisting of alternating arrays of six-membered Si rings, which can be converted into a direct gap semiconductor of 0.86 eV by applying a low tensile strain (~ 2.5%). Our calculations revealed that the photovoltaic efficiency of the tri-layer silicene reaches 29% at 1.0 µm, which is comparable to that of bulk GaAs with the highest conversion efficiency among thin-film solar cell absorbers. Graphical abstract: fx1 Highlights: A quasi-direct gap tri-layer silicene is predicted through swarm-intelligence structure-searching method. The tri-layer silicene can be converted into a direct gap semiconductor of 0.86 eV by applying a low tensile strain (~ 2.5%). The calculated photovoltaic efficiency of the tri-layer silicene reaches 29% at thickness of 1.0 µm.